The Designation and Removal of Trustee Stock Status: Wealth Effects - DING, David K. (Institutional Knowledge at Singapore Management University, 2000)
This study investigates the impact of trustee stock status announcements on shareholders' wealth in Singapore. An event study methodology is used to ascertain the abnormal returns around the announcement day. The results show that there is a positive and permanent wealth effect on trustee stocks resulting from designation announcements. Conversely, when trustee stocks lose their status, the significant negative abnormal returns suggest that shareholders' wealth is adversely affected. This reaction, however, appears to be a temporary phenomenon and is not simply a mirror image of designation announcements. The differences in the underlying regulatory structures partially explain the findings.